Elbow lameness in dogs of six years and older - Vermote, K. A. G.; Bergenhuyzen, A. L. R.; Gielen, I.; van Bree, H.; Duchateau, L.; Van Ryssen, B. (Veterinary and Comparative Orthopaedics and Traumatology, 2010)
Objectives: To report on the frequency and distribution of lesions of the medial coronoid process in dogs of six years of age and older, and to describe the arthroscopic findings in the affected joints. To compare those lesions seen in ‘old’ dogs with those seen in ‘young’ dogs between the ages of five and 18 months.Methods: A retrospective study of dogs six-years-old and older admitted for elbow lameness and subsequent elbow arthroscopy. The dogs were divided into groups according to the lesions of the medial coronoid process diagnosed during arthroscopic examination and computed tomography (CT). The radio-graphic degree of osteoarthritis (OA) and arthroscopically diagnosed lesions on the medial humeral condyle are described.Results: In 51 ‘old’ dogs, five types of lesions could be identified on arthroscopy and CT: chondromalacia-like lesions (2%), fissures (27.5%), non-displaced fragments (12%), displaced fragments (27.5%), and erosions within the medial compartment without fragmentation (31%). A significantly different distribution of lesions was seen in ‘young’ dogs: fissures (23%), non-displaced fragments (45%), displaced fragments (29%), and erosions within the medial compartment without fragmentation (3%). No difference in radio-graphic degree of OA was seen between the two groups.Clinical significance: This study demonstrates the relatively high incidence of medial coronoid disease in dogs older than six years of age, and it highlights one particular problem in ‘old’ dogs: the complete erosion of the medial compartment.
Keywords: Elbow joint; arthroscopy; medial coronoid process; old dogs